Cerebral Perfusion Pressure in Severe Traumatic Brain Injury and Its Relation to Microdialysis-Assessed Interstitial Brain Glycerol and Lactate-Pyruvate Ratio - Singla, Raghav; Gupta, Deepak; Borkar, Sachin A.; Suri, Ashish; Kale, Shashank S.; Sharma, Bhawani S. (Indian Journal of Neurotrauma, 2016)
Objective The aim of the study was to analyze the relationship of cerebral perfusion pressure (CPP) and its relationship to microdialysis (MD) analysates and their role as predictors of outcome in severe traumatic brain injury (TBI).Methods A total of 41 patients with severe TBI who underwent decompressive craniectomy were prospectively monitored with intracerebral MD catheters. The relation between cerebral perfusion pressure and MD-measured interstitial brain glycerol and lactate-pyruvate ratio (LPR) concentrations was studied.Results Twenty-six (63.4%) patients had a good outcome in terms of GOS at 6 months whereas the rest (15 patients) had poor GOS at 6 months. There was significant difference in mean CPP values between the two groups (p = 0.000). In the poor outcome group, the mean LPR was 80.16 as compared with a mean of 45.77 in the good outcome group (p = 0.00). Taking a cutoff of both LPR < 45 and CPP > 70 mm Hg, a significant difference in outcome was seen (p = 0.03).Conclusion CPP seems essential to maintaining normal metabolism. Low CPP values and high ICP values are associated with a poor outcome. MD variables glycerol and LPR are dependent on CPP and are prognostic factors for the outcome.
Keywords: microdialysis; glycerol; lactate-pyruvate ratio; cerebral perfusion pressure